DAYA DUKUNG LINGKUNGAN TERKAIT PENGOLAHAN LIMBAH BATIK DI KAMPUNG BATIK GIRILOYO, KABUPATEN BANTUL, YOGYAKARTA - I Gusti Ayu Dwi Muliasari; Widiastuti (ATRIUM: Jurnal Arsitektur, 2020)
Title: Carrying Capacity Related to Batik Waste Processing in Giriloyo Batik Village, Bantul District, Yogyakarta Yogyakarta is one of the areas in Indonesia that still maintains its cultural heritage, one of the cultural heritages that is still a source of pride is Batik. This cultural heritage is increasingly in demand by many people because of its very diverse motives and usually these batik motifs describe the characteristics of an area so that they can be used as souvenirs. This higher market demand has made batik production increase, causing new problems, namely environmental pollution as a result of the waste of batik making itself. The purpose of this study was to determine how to dispose of batik waste in Kampung Batik Giriloyo, Yogyakarta, and to analyze its impact on environmental quality. This research uses qualitative research methods with a case study approach. The results showed that some of the batik home producers still dispose of their waste directly into the river, some of them dispose of it in wells without filtration, and some have disposal sites that meet standards. Discharge in the river results in dirty river water and causes the fish in it to die. Direct dumping into the soil causes the surrounding plants to die. Meanwhile, disposal in soil wells without filtration causes soil contamination and there is a concern that it will contaminate nearby well water.